Implementation of Antimicrobial Stewardship Activities in India - Arzoo Sahni; Arti Bahl; Rashi Martolia; Sudhir Kumar Jain; Sujeet Kumar Singh (Indian Journal of Medical Specialities)
Introduction: The ease of availability of antimicrobials and their excessive use is a growing issue which has significantly contributed to antimicrobial resistance (AMR). This is a matter of public health concern as the burden of AMR is far outpacing the research and development work done to develop new antimicrobials. India, being one of the top consumers of antimicrobials, now faces this threat which can only be curtailed through the implementation of antimicrobial stewardship program (AMSP). To address this issue, this systematic review attempts to study the implementation activities of AMSP in the country by the means of literature review. Methods: A comprehensive research using web-based search engines was performed employing a combination of search string: AMSP, ASP, implementation, impact, antibiotic stewardship, antimicrobial surveillance, infection control, and resistance control. The search yielded thirty papers between the time period of 2008 and 2019. 17 papers fulfilling the inclusion-exclusion criteria were taken up for review, employing PRISMA framework. Results: Results from different studies conducted on implementation of AMSP and its components were consolidated and analyzed to track the extent of AMSP activities. Moreover, by studying AMSP practices, gaps in implementation activities were identified by highlighting the AMSP components that were not fully utilized in the country. Conclusion: The results show that implementation of AMSP in India is still in its nascent stage as all the stewardship components are yet to be fully applied in the country. There seems to be a lot of scope in improving the implementation activities by building and strengthening of components such as use of information technology in monitoring and surveillance, use of antibiotic cycling and sensitizing staff, and broadening the role of different staff members to develop an effective program in the nation which meets the goals of National Action Plan-AMR.